Cerebral ischemia and basic mechanisms - Hartmann, Alexander; Yatsu, Frank M.; Kuschinsky, Wolfgang (Springer Berlin Heidelberg, 1994)
This documentation of an international conference on the underlying process of cerebral ischemia contains extensive reviews and new data on methodology and results of measurement of cerebral blood flow and cerebral metabolism in cerebral ischemia. Cellular processes involved in ischemiaof the brain are covered as well as new techniques for discovery of dynamic changes in acute ischemia of the brain. Therapeutic consequences are desribed with respect to their newest findings
Keywords: Konferenzschrift -- Bodensee, 1992 -- Schachen, Lindau; Pathophysiologie; Ischämie; Hirnkrankheit